UPAYA PENCEGAHAN ANEMIA MELALUI PEMBERIAN SUSU KEDELAI DAN KURMA PADA REMAJA PUTRI DI SMK BAITUL HIKMAH TEMPUREJO - anggraeni, Ernawati; Handayani, Yuni; Sari, Melati Puspita; Dewi, Yashinta Kumala (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Anemia is a decrease in the capacity of the blood to carry oxygen due to a less than normal number of red blood cells or a decrease in hemoglobin concentration which can be caused by a decrease in the production of red blood cells or a lot of blood loss. Anemia in Indonesia is generally caused by iron deficiency, so it is more often called iron deficiency anemia. Anemia is a condition in which a person has a hemoglobin (Hb) level of <13g/dL for males or <12g/dL for females. This disease is the highest cause of disability in the world. The aim of this activity is to prevent anemia through giving soy milk and dates to anemic young women at Baitul Hikmah Tempurejo Vocational School, Jember. The method of delivering health education is carried out by means of a question and answer discussion to all respondents. The results of community service activities have provided education to young women through lectures, checking Hb levels, discussing the importance of preventing anemia. The responses generated by the respondents were enthusiastic enough to be understood by teenagers. This is evidenced by the questions and answers from the respondents. A screening test for hemoglobin (Hb) levels was carried out. From the results of the examination, not all adolescents with normal Hb levels, some were in the anemia category, the hemoglobin level was checked using an electric detection device. Treatment has been given by giving date soy milk to adolescents with anemia, then re-evaluation was carried out and the results showed an increase in Hb levels.